(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
the poetics of expressing the artistic landscape of the world through floristic images has been formed since ancient times. Their role in literary and artistic works is incomparable in illuminating social life and vividly embodying people’s lifestyle. Floristic images are often found in Uzbek literature, especially classical poetry. Their genesis goes back to folklore works. People’s feelings are expressed through these images in folk lyrics. The role of flora images in classical poetry is studied in the article. Examples of poetic fragments belonging to the works of bright representatives of Uzbek classic lyric were taken and deeply scientifically analyzed within the scope of the topic.